A189 A RETROSPECTIVE ANALYSIS OF OUTCOMES ASSOCIATED WITH PEGYLATED-INTERFERON (PEG-IFN) TREATMENT IN CHRONIC HEPATITIS B (CHB). (1st March 2018) - Syed, A; Lee, S; Israelson, H; Pinto, J; Coffin, C S
Abstract: Background: PEG-IFN is first-line therapy for CHB offering the advantage of a finite treatment, but is rarely used due to concerns about tolerability and efficacy. Nucleot(s)ide analogues (NUC) therapy are well tolerated but require prolonged therapy, with significant cost as well as potential for long-term adverse effects. Aims: We aim to assess tolerability and long term outcomes in treatment-naive patients who received PEG-IFN for CHB. The primary outcome assessed was durability of off-treatment response (i.e. HBV DNA<2000 IU/mL, normal ALT). Secondary outcomes assessed included the proportion of those who required subsequent NUC therapy, quantitative HBV surface antigen (qHBsAg) levels, and the proportion with side effects. Methods: In this retrospective cohort study, CHB patients who received antiviral therapy from January 1st, 2007 - July 1st, 2017 were identified via the Calgary Liver Unit Hepatitis B database. Data collected included age, sex, ethnicity, FibroScan® results, labs (HBV DNA, genotype, qHBsAg, ALT), total treatment duration, on treatment virological response (HBV DNA and qHBsAg if available) and reported side effects. Patients co-infected with hepatitis D treated with Peg-IFN (n=4) were excluded. Results: In total, 893 patients were started on a NUC, of which 50 (5.6%) patients received PEG-IFN therapy, including 3 currently on treatment who were excluded. The patients' had the following demographics: median age 43 ± 9.3 years, 72.3% male, 80.8% East Asian, and 57% with unknown genotype. 70.2% (33/47) completed the 48 week course of PEG-IFN therapy. From the 29.2% (14/47) who discontinued interferon early, 64.2% did so due to treatment failure and 21.4% due to side effects. 21/47 (44.7%) who received PEG-IFN did not require subsequent NUC treatment during median follow-up of 33.9 months (±27.5, range 0.9–82.1). 85.7% had normal ALT and 61.9% had DNA levels <2000 IU/mL on most recent follow-up. 55% (26/47) of patients treated with PEG-IFN had a virological and biochemical rebound requiring initiation of a NUC within a median of 18.7 months (±15.6, range 3.2–55.4) post PEG-IFN treatment. In those with sustained response to Peg-IFN, 16/21 had available end of treatment qHBsAg that showed that 8/16 (50%) had levels <1000 IU/mL (median 986.5 ± 1973.3, range 1.2-6384). 24/26 patients who failed PEG-IFN had end of treatment qHBsAg that showed 5/24 (20.8%) had levels <1000 IU/ml (median 3449.5 ± 13661.5, range 3.9-63511). Difference between the two groups was not statistically significant. Conclusions: A significant proportion (44.7%) of patients treated with Peg-IFN showed a SVR, including low qHBsAg levels (<1000 IU/mL), indicating robust immune control of HBV. Careful patient selection and adherence to treatment discontinuation rules based on qHBsAg levels will optimize management usage of PEG-IFN therapy for CHB. Funding Agencies: None